N‐Heterocyclic‐based adsorbents for antibody purification—effect of ligand structure. Issue 5 (20th March 2014) - Mountford, Simon J.; Daly, Rachel; Campi, Eva M.; Bhagwat, Anjali; Robinson, Andrea J.; Hearn, Milton T. W.
<x xml:space="preserve">Abstract</x> A new set of ligands based on substituted pyridine and other N‐heterocyclic structures, possessing an aliphatic primary amino group tether and an exocyclic sulphur atom, has been prepared and immobilized onto epoxy‐activated matrices such as Sepharose 6 Fast Flow®. The derived adsorbents have been evaluated for their utility to capture and purify humanized monoclonal antibodies. Favourable binding properties were assessed from screening assays to determine optimal conditions for the capture and elution of the monoclonal antibodies. Static and dynamic binding experiments were employed to derive the equilibrium dissociation constants KD's and binding capacities Qmax's. Typically, the KD values were in the range of 2–5 μM and the Qmax values between 20 and 75 mg mAb/ml resin, depending on the stereo‐electronic properties of the substituent in the N‐heterocyclic ring structure. The effect of ligand structure on the selectivity of these adsorbents was also investigated, and criteria for their use in the purification of monoclonal antibodies from cell culture supernatants established. Copyright © 2014 John Wiley & Sons, Ltd.